Unlocking the potential of stem cells: Their crucial role in the production of cultivated meat - Dong-Kyung Lee; Minsu Kim; Jinsol Jeong; Young-Seok Lee; Ji Won Yoon; Min-Jeong An; Hyun Young Jung; Cho Hyun Kim; Yelim Ahn; Kwang-Hwan Choi; Cheorun Jo; Chang-Kyu Lee (Current Research in Food Science, 2023)
Cellular agriculture is an emerging research field of agribiotechnology that aims to produce agricultural products using stem cells, without sacrificing animals or cultivating crops. Cultivated meat, as a representative cellular product of cellular agriculture, is being actively researched due to global food insecurity, environmental, and ethical concerns. This review focuses on the application of stem cells, which are the seeds of cellular agriculture, for the production of cultivated meat, with emphasis on deriving and culturing muscle and adipose stem cells for imitating fresh meat. Establishing standards and safety regulations for culturing stem cells is crucial for the market entry of cultured muscle tissue-based biomaterials. Understanding stem cells is a prerequisite for creating reliable cultivated meat and other cellular agricultural biomaterials. The techniques and regulations from the cultivated meat industry could pave the way for new cellular agriculture industries in the future.